Green technologies and environmental sustainability - Ritu, Singh; Kumar, Sanjeev (New York, NY : Springer International Publishing, 2017)
Providing different perspectives on green technology in sectors like energy, agriculture, waste management and economics, this book contains recent advances towards sustainable development in bioenergy, nanotechnology, green chemistry, bioremediation, degraded land reclamation. It is aimed at a broad academic and industrial readership
Chapter 1. A review and perspective of constructed wetlands as a green technology in decentralization practices.- Chapter 2. Laccases: A Blue Enzyme for Greener Alternative Technologies in the Detection and Treatment of Emerging Pollutants.- Chapter 3. Biofuels for Sustainable Development-A Global Perspective.- Chapter 4. Greening the Indian Transport Sector: Role of biodiesel.- Chapter 5. Microalgae biofuels: A green renewable resource to fuel the future.- Chapter 6. Harvesting of Microalgae for Biofuels: comprehensive performance evaluation of natural, inorganic and synthetic flocculants.- Chapter 7. Solar Energy Harvesting Solar photovoltaics (PV): A sustainable solution to solve energy crisis.- Chapter 8. Biological limitations on Glyphosate Biodegradation.- Chapter 9. Bioindication-based approaches for sustainable management of urban ecosystems.- Chapter 10. An Overview of Sustainable Dimensions and Indicators for Smart City.- Chapter 11. Need for an integrated approach towards environmental quality control in developing countries.- Chapter 12. Eco-friendly Post-consumer waste management utilizing Vermi-technology.- Chapter 13. Recent Advancement in Green Sustainable Nanocellulosic Fiber: An overview.- Chapter 14. Metal NPs (Au, Ag & Cu): Synthesis, stabilization & their role in green chemistry and drug delivery.- Chapter 15. Green Synthesis of Nanoparticles: An Emerging Phyotechnology.- Chapter 16. Green analytical techniques- Novel and Aboriginal perspectives on Sustainable Development.- Chapter 17. Emerging aspects of bioremediation of arsenic.- Chapter 18. Distillery wastewater: A major source of environmental pollution and it's biological treatment for environmental safety.- Chapter 19. Ecological Restoration techniques for management of degraded, mined-out areas and the role played by rhizospheric microbial flora-A review of case studies from India.- Chapter 20. Biochar: An Emerging Panacea for Contaminated and Degraded Soil.
Includes bibliographical references and index.
Keywords: Sustainable living; Environmentalism; Green technology